Value-added factors for economical evaluation of mineral deposits development - V. I. Lisov; Z. M. Nazarova; A. A. Mautina; V. M. Zaernyuk (Известия высших учебных заведений: Геология и разведка, 2015)
The existing practice of the prices management at foreign enterprises, concerning mineral resources and concentrates, explored at Russian mineral deposits, is considered. The economical consequences of such state of affairs are shown. The authors point, concerning the use of value-added factor in economical evaluation of mineral deposits development, is described.